Hierarchy, power, and strategies to promote cooperation in social dilemmas - Catherine Molho; Daniel Balliet; Junhui Wu (Games, 2019)
Previous research on cooperation has primarily focused on egalitarian interactions, overlooking a fundamental feature of social life: hierarchy and power asymmetry. While recent accounts posit that hierarchies can reduce within-group conflict, individuals who possess high rank or power tend to show less cooperation. How, then, is cooperation achieved within groups that contain power asymmetries? To address this question, the present research examines how relative power affects cooperation and strategies, such as punishment and gossip, to promote cooperation in social dilemmas. In two studies involving online real-time interactions in dyads (N = 246) and four-person groups (N = 371), we manipulate power by varying individuals' ability to distribute resources in a dictator game, and measure punishment, gossip, and cooperative behaviors in a multi-round public goods game. Findings largely replicate previous research showing that punishment and gossip opportunities increase contributions to public goods in four-person groups. However, we find no support for the hypotheses that power directly affects cooperation or the use of punishment and gossip to promote cooperation. We discuss the implications of these findings for understanding the influence of hierarchy and power on cooperation within dyads and groups.
http://dx.doi.org/10.17605/OSF.IO/SPHN6
Keywords: 330; experimental games; power; cooperation; punishment; gossip